2021
DOI: 10.3390/nu13092969
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemoradiotherapy Induces Body Composition Changes in Locally Advanced Head and Neck Squamous Cell Carcinoma: Comparison between Oral Cavity and Non-Oral Cavity Cancer

Abstract: Few prospective cohort trials have evaluated the difference in treatment-interval total body composition (TBC) changes assessed by dual-energy X-ray absorptiometry (DXA) between two patient subgroups with locally advanced head and neck squamous cell carcinoma (LAHNSCC) receiving concurrent chemoradiotherapy (CCRT): oral cavity cancer with adjuvant CCRT (OCC) and non-oral cavity with primary CCRT (NOCC). This study prospectively recruited patients with LAHNSCC. Clinicopathological variables, blood nutritional/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
3
2
0
Order By: Relevance
“…To address these uncertainties, in the current study, we adopted calorie supply programs recommended by academic societies for patients with LAHNSCC undergoing CCRT and found that the change in TBM during CCRT correlated with that in certain NIBs (OCC Factor 3 correlated with Δplatelet count, and NOCC Factor 3 correlated with Δalbumin and ΔCRP). In addition, the mean daily calorie intake during CCRT was associated with changes in TBM and TBF, which is compatible with our previous observation [ 35 ]. Finally, we showed that the treatment interval change in TBM (OCC Factor 3) independently contributed to the 2-year mortality rate.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To address these uncertainties, in the current study, we adopted calorie supply programs recommended by academic societies for patients with LAHNSCC undergoing CCRT and found that the change in TBM during CCRT correlated with that in certain NIBs (OCC Factor 3 correlated with Δplatelet count, and NOCC Factor 3 correlated with Δalbumin and ΔCRP). In addition, the mean daily calorie intake during CCRT was associated with changes in TBM and TBF, which is compatible with our previous observation [ 35 ]. Finally, we showed that the treatment interval change in TBM (OCC Factor 3) independently contributed to the 2-year mortality rate.…”
Section: Discussionsupporting
confidence: 92%
“…Dual-energy X-ray absorptiometry (DXA) can be used to appropriately evaluate the status of three major components of TBC: lean body mass (LBM), total fat mass (TFM), and total body bone mineral content at the time of cancer diagnosis and during treatment [ 7 , 18 , 28 , 29 , 30 ]. In accordance with findings from other reports [ 7 , 25 , 31 , 32 , 33 , 34 ], we observed that the LBM and TFM assessed using DXA were significantly decreased among patients with LAHNSCC during CCRT [ 35 , 36 ]. Furthermore, a low pretreatment muscle mass is associated with increased treatment-related toxicity, early treatment failure, and recurrence-free survival among patients with LAHNSCC [ 35 , 36 , 37 ].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Alterations in total body composition (TBC), assessed by dual-energy X-ray absorptiometry (DXA), are commonly observed in cancer patients in response to various physiological and pathological stimuli, such as aging, sex, intercurrent illness, metabolic disturbance, and therapy; therefore, they can appropriately reflect the status of nutritional and inflammatory changes caused by cancer or treatment. We observed a significant loss in lean body muscle (LBM) and total fat mass (TFM) in patients with LAHNSCC during CCRT [39,40]. Additionally, the pretreatment level and treatment-interval changes in TBC are associated with increased treatment-related toxicity, early treatment failure, recurrence-free survival, and two-year mortality rate among LAHNSCC patients undergoing CCRT [39][40][41][42].…”
Section: Introductionmentioning
confidence: 97%
“…We observed a significant loss in lean body muscle (LBM) and total fat mass (TFM) in patients with LAHNSCC during CCRT [39,40]. Additionally, the pretreatment level and treatment-interval changes in TBC are associated with increased treatment-related toxicity, early treatment failure, recurrence-free survival, and two-year mortality rate among LAHNSCC patients undergoing CCRT [39][40][41][42]. Therefore, further research is needed to investigate the effect of TBC changes on treatment interruption in patients with LAHNSCC undergoing CCRT.…”
Section: Introductionmentioning
confidence: 98%